The 8088 and 8086 microprocessors programming, interfacing, software, hardware, and applications : includes the 80286, 80386, 80486, and Pentium processors - Triebel, Walter A. (Prentice Hall, 1997)
For one or two-semester courses in Microprocessors or Intel 16-32 Bit Chips. Future designers of microprocessor-based electronic equipment need a systems-level understanding of the 80x86 microcomputer. This text offers thorough, balanced, and practical coverage of both software and hardware topics. Basic concepts are developed using the 8088 and 8086 microprocessors, but the 32-bit versions of the 80x86 family are also discussed. The authors examine how to assemble, run, and debug programs, and how to build, test, and troubleshoot interface circuits.